E-064 Endovascular treatment of acute vertebro-basilar occlusion with self-expandable stents: single center experience. (4th July 2012) - Dabus, G; Samaniego, E; Linfante, I
Abstract : Objective: The rate of death or disability associated with acute basilar artery occlusion (BAO) is as high as 80%–90% with standard medical therapy. We report our single center experience in the treatment of acute BAO with self-expandable stents (SES). Method: The stroke database of our institution was retrospectively reviewed from June of 2008 to February of 2012. Patients with angiographic evidence of symptomatic BAO in whom SES were attempted to deploy as acute endovascular intervention were included in the analysis. Good outcome was defined as a modified Rankin Scale ≤2 on follow-up. Results: Ten patients with acute BAO in whom stents were attempted to deploy were identified. Median National Institute of Health Stroke Scale score on admission was 18. The average of time from symptom onset to endovascular treatment was 11 h after any vertebro-basilar ischemic symptoms had started. Pre-procedure, all patients had a TIMI score of 0. Stents were successfully deployed in 90% (9/10) of cases. One stent was not deployed due to severe vessel tortuosity. Twelve stents were deployed in nine subjects. Seven out of 10 patients (70%) had a TIMI score of 3 at the end of the procedure. The rate of procedural complications was 20% (2/10). Two patients developed intracerebral hemorrhage due to wire perforations. Fifty percent patients (5/10) achieved good outcome (mRS ≤2) on follow-up. Four patients died and one had severe disability. Conclusions: The use of SES in this small cohort of patients with acute BAO is technically feasible with high recanalization rates. The safety and efficacy of the procedure need to be addressed in larger randomized controlled study. Competing interests: G Dabus: Codman Neurovascular. Surpass Medical. E Samaniego: None. I Linfante: Codman Neurovascular. Surpass Medical.